ŻYCIE I TWÓRCZOŚĆ WŁADIMIRA KORWIN-PIOTROWSKIEGO - Venclova, Tomas; Dubyk, Halyna (Colloquia Litteraria, 2019)
“Life and Writings of Vladimir Krowin-piotrowski” The paper presents a profile of Vladimir Krowin-Piotrowski, a significant twentieth century poet, now forgotten. He is known mostly to researchers of the emigre literature, as he played a key role in the short lived flourishing of ‘Russian Berlin’, when he was part of the inner circle of Vladimir Nabokov.